The best of the year - modern romance 2016. (2017) - Williams, Cathy; Graham, Lynne; Lee, Miranda; Kendrick, Sharon; James, Julia; Green, Abby; Hewitt, Kate; Yates, Maisey; Lucas, Jennie; Blake, Maya; et al
No abstract available